The donation contract and its exceptions regarding the restriction of the reserved portion of the estate (Research, Society and Development, 2022)
This paper deals with the donation contract and its exceptions regarding the inheritance reserve. In this context, we will address the conceptual issues of the donation contract, its species, its succession reflexes and the peculiarities of the remunerative donation in face of the property limitations imposed by the legal system as a way to ensure the legitimate reserve of the necessary heirs. The study of the chosen theme is important because it brings real implications to succession law, which must be observed in the social, economic and legal reality. The difficulties in relation to the matter lie in the existing controversies in the doctrine and in the jurisprudence, since it is discussed whether the remunerative donation should or should not obey the unavailable part of the legitimate necessary. Among the difficulties pointed out, this paper aims to solve these controversies and demonstrate that the remuneration donation is a special donation that is restricted to the reserved portion of the estate only in that which exceeds the value of the services rendered. The methodology used was bibliographical research, with a qualitative approach, with a descriptive objective, with the purpose of proposing a formative evaluation. We conclude that the theme is foreseen in the legal system, in the most classical doctrine and in the jurisprudence of the Superior Court of Justice.